Assessment of orthodontic treatment need: a comparison of study models and facial photographs - Sherlock JM, Cobourne MT, McDonald F. (Blackwell Synergy, 2008)
The current study aims to examine how orthodontic treatment need is prioritized depending upon whether dental study models or facial photographs are used as the means of assessment.